OP0087 Platelet-specific fli1-knockout mice show accelerated wound closure associated with increased myofibroblast formation in the inflammatory phase. (15th June 2017) - Hirabayashi, M; Asano, Y; Yamashita, T; Saigusa, R; Miura, S; Nakamura, K; Miyagawa, T; Ichimura, Y; Taniguchi, T; Yoshizaki, A; Sato, S
Abstract : Background: Systemic sclerosis (SSc) is a systemic connective tissue disease characterised by autoimmunity, vascular disorder and fibrosis of skin and other organs (1). Although substantial reports have been hitherto provided upon its pathogenesis in relation to microvasculature, among which are on endothelial and fibroblastic Fli1 deficiencies (1, 2), adequate investigation into hemocytic involvement is yet to be attained. Platelets are well known for its function in hematostasis whereas they also play a part in inflammation, immunity and cellular proliferation (3), thus prompting us to speculate their cardinal role in the development of the disease. Objectives: Here we aim to unravel the role of platelets in the pathogenesis of SSc, with generation of platelet-specific conditional Fli1 knockout ( Fli1 PcKO) mice to scrutinise its dermal wound healing process. Methods: We generated Fli1 PcKO mice using the Cre-Lox system along with PfCre +/- mice as an appropriate control. We made two excisional wounds on the dorsal skin of each mouse (three months old) using an eight-millimeter-diameter punch and traced the wound surfaces every other day to measure their areas using Image J until all the wounds were epithelised. On a separate experiment, perilesional skin was harvested on the day two, from which we extracted mRNA for the measurement of proinflammatory and profibrotic cytokines. An immunostaining for α-SMA was performed on the skin samples. Results: The areas of the wounds were calculated and shown in ratio to their initial areas (day 0). Fli1 PcKO mice showed a significant decrease in the areas compared to the control on day 2. mRNA measurement revealed a significant increase in Mmp13 and significant decreases in Tgfb1, Ifng and Il13 for Fli1 PcKO. In histopathology, α-SMA positive fusiform-shaped cells were abundant in the granulation tissue of Fli1 PcKO mice (Figure; left, PfCre +/-; right, Fli1 PcKO; original magnification, ×400). Conclusions: In dermal injuries on Fli1 PcKO mice, inflammatory disturbances precipitate myofibroblast formation in the granulation tissue, thus anticipating wound closure by mechanical contraction. References: Asano Y et al., Curr Rheumatol Rep. 2013; 15(12):382. Asano Y et al. Am J Pathol. 2010; 176(4):1983–98. Ramirez GA et al., Front Immunol. 2012; 3:160. Disclosure of Interest: None declared